1976
DOI: 10.2343/geochemj.10.1
|View full text |Cite
|
Sign up to set email alerts
|

Major elements and REE in tektites and three probable shock-metamorphic rock series of the Baltic shield.

Abstract: REE contents of four tektites from separate strewn-fields have been determined and the REE and major elements in ten shock-metamorphic rocks from lakes Lappajarvi , Saaksjarvi (Finland), and Tinisjarvi (Soviet Karelia). Neither the impact of meteorite or comet nor secondary weathering seems to change the REE content or distribution pattern in rocks. Therefore, where the texture and major element compo sition in country rock has changed through impact and after it, REE can be used as indicators of the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…The differences among the REE patterns of target and impact melt rock samples might appear in contrast to the results of other authors (Koljonen and Rosenberg 1976;Koeberl et al 1985;Koeberl 1986;Val'ter and Kolesov 1990), who showed that the REE in vitreous impactites and tektites associated with meteorite craters usually have a concentration and composition strongly similar to the REE level and distribution of the target rocks. In particular, French et al (1997) pointed out that the REE pattern of Gardnos impactites closely follows that of the granitic gneiss target rock.…”
Section: Rare Earth Elements (Ree)contrasting
confidence: 72%
“…The differences among the REE patterns of target and impact melt rock samples might appear in contrast to the results of other authors (Koljonen and Rosenberg 1976;Koeberl et al 1985;Koeberl 1986;Val'ter and Kolesov 1990), who showed that the REE in vitreous impactites and tektites associated with meteorite craters usually have a concentration and composition strongly similar to the REE level and distribution of the target rocks. In particular, French et al (1997) pointed out that the REE pattern of Gardnos impactites closely follows that of the granitic gneiss target rock.…”
Section: Rare Earth Elements (Ree)contrasting
confidence: 72%
“…The contents are higher than in common magmatic (e.g., granites, REE 237 ppm, La i Yb ^ 10, Koljonen and Rosenberg 1976) and metamorphic rocks or in clastic sediments (see Ronov et al 1974). The La/Yb ratio (23-41, Table 4) is higher than in common rock and sediment types 1-20, see Koljonen and Rosenberg 1976), indicating that during the exogenic migration the REE differentiate from each other, the heavy REE (Gd -Lu) migrating faster than the light (La -Sm). This seems to be a general rule which controls the migration of REE and brings about the enrichment of light REE ill the continents during the evolution of Earth's crust.…”
Section: Chemical Compositionmentioning
confidence: 72%